1996
DOI: 10.1021/ja951393i
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular H Atom Transfer Reactions in Alkyl Radicals and the Ring Strain Energy in the Transition Structure

Abstract: Ab initio calculations were performed on prototypical intramolecular H atom transfer reactions in alkyl radicals, namely, the identity reactions of 1,2-, 1,3-, 1,4-, and 1,5 intramolecular isomerizations in the ethyl, 1-propyl, 1-butyl, and 1-pentyl radicals, respectively. The equilibrium geometries and the transition structures have been optimized at the UHF/6-31G* and/or UMP2/6-311G** levels. The activation energies at 0 K were calculated with the MP-SAC2 and BAC-MP4 methods. The computed barrier heights (41… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
68
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 23 publications
9
68
0
Order By: Relevance
“…We are aware of the work by Viskolcz et al [45,46] to develop such rules, but that work ignored hindered rotations, which can be important for detemining Arrhenius A-factors; the "rotor loss" effects are included in the rules of Table II. Parameters for H-shift types not listed (e.g., 1,3 secondary to allylic radical) were estimated by Evans-Polanyi rules derived from the results of the above ab initio calculations, combined with an estimate of the ring-strain energy for the particular H-shift transition state to predict the activation energy:…”
Section: Modified Arrhenius Parametersmentioning
confidence: 99%
“…We are aware of the work by Viskolcz et al [45,46] to develop such rules, but that work ignored hindered rotations, which can be important for detemining Arrhenius A-factors; the "rotor loss" effects are included in the rules of Table II. Parameters for H-shift types not listed (e.g., 1,3 secondary to allylic radical) were estimated by Evans-Polanyi rules derived from the results of the above ab initio calculations, combined with an estimate of the ring-strain energy for the particular H-shift transition state to predict the activation energy:…”
Section: Modified Arrhenius Parametersmentioning
confidence: 99%
“…However, nonArrhenius behavior may occur at intermediate temperatures when equilibration of the addition path competes with abstraction. Further complications appear when larger alkyl radicals are involved since the barriers for internal 1,4 and 1,5 H-atom transfers are low [9,10].…”
Section: Reverse Decomposition -Additionmentioning
confidence: 99%
“…Earlier, we studied a large family of unimolecular reactions of alkyl radicals, the internal H-atom transfers via cyclic transition states extensively [9,10]. We found kinetic parameters for these reactions which are generally useful for the modeling of complex systems [11].…”
Section: Introductionmentioning
confidence: 99%
“…They can be formed by a first H • transfer from the chain to an ionized heteroatom [5] or by ring opening as studied by Tabet and coworkers [9]. From experiment [5,9,10] and from calculation [11], it has been also shown that the energy barrier for the transfers to a carbon radical site decreases from the 1,2-H • migration up to the 1,5 one. More generally, the energy barrier for intramolecular 1,n-H • transfers is the lowest when the hydrogen to be transferred, the acceptor atom and donor atom are in line in the transition state.…”
Section: Introductionmentioning
confidence: 96%